MicroRNAs in Neural Stem Cells and Neurogenesis - Kawahara, Hironori; Imai, Takao; Okano, Hideyuki (Frontiers in Neuroscience, 2012)
MicroRNA (miRNA) is a type of short-length (~22 nt) non-coding RNA. Most miRNAs are transcribed by RNA polymerase II and processed by Drosha-DGCR8 and Dicer complexes in the cropping and dicing steps, respectively. miRNAs are exported by exportin-5 from the nucleus to the cytoplasm after cropping. Trimmed mature miRNA is loaded and targets mRNA at the 3' or 5' untranslated region (UTR) by recognition of base-pairing in the miRNA-loaded RISC, where it is involved in gene silencing including translational repression and/or degradation along with deadenylation. Recent studies have shown that miRNA participates in various biological functions including cell fate decision, developmental timing regulation, apoptosis, and tumorigenesis. Analyses of miRNA expression profiles have demonstrated tissue- and stage-specific miRNAs including the let-7 family, miR-124, and miR-9, which regulate the differentiation of embryonic stem (ES) cells and/or neurogenesis. This review focuses on RNA-binding protein-mediated miRNA biogenesis during neurogenesis. These proteins have also been linked to human diseases because their mutations can cause several nervous system disorders. Moreover, defects in core proteins involved in miRNA biogenesis including Drosha, DGCR8, and Dicer promote tumorigenesis. Thus, the study of not only mature miRNA function but also miRNA biogenesis steps is likely to be important.